The Global Child Nutrition Foundation reported that school meals around the world are a somewhat underutilized channel for providing key micronutrients to children and suggests awareness raising around biofortified foods - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The report was based on the 2019 Global Survey of School Meal Programs and is the only global database on this topic. HarvestPlus provided data and supplementary information.